Ending Famine in India : A Transnational History of Food Aid and Development, C. 1890-1950. - Simonow, Joanna. (Global Connections: Routes and Roots Series, 2023)
The task of ending famine in India was taken up by many at the beginning of the twentieth century. Only decades earlier, famine in India had been believed to be a necessary evil. Now it was the reason for the increasing activities of doctors, nutritionists, social reformers, agricultural experts, missionaries, anti-colonial activists and colonial administrators, all involved in temporary relief and finding permanent solutions to famine.The involvement of this panoply of historical actors places Indian famines in the centre of the converging histories of humanitarianism, development, nutrition and (anti-) colonialism. Tracing their activities renders such convergences visible and pushes the boundaries of the history of famines in South Asia beyond its common spatial and temporal frames. Ending Famine in India examines the tripartite relationship of India, Britain and the United States, linking the late-Victorian holocausts with the struggle for food security in the 1950s.